Educational media in secondary schools : an examination of existing facilities and the relationships between selected teachervariables and media utilization - Fatimah, Abu Bakar (1980)
This study seeks to empirically establish the status of media setting in schools, the rcIat ionships between media utilisation and certain teacher variables known to influence media utilisation and the barriers to media use perceived by teachers. Setting for media use consisted of media equipment and materials collections, presence of media related facilities and nature of media r e l at ed services provided. Teacher variables chosen were teachers' professional characteristics.